Indigenous adaptation to a rapidly changing economy : (CIDSE Cambodia)
Text in English and Kmer. A paper presented at the National Conference on Landlessnes and Development, 22-24 August, Phnom Penh. Oxfam GB, Cambodia Land Study Project ; mini case study 3.